Evaluating impacts of intelligent transit priority on intersection energy and emissions. (September 2020) - Liu, Haofei; Zhang, Yi; Zhang, Yi; Zhang, Kai
Highlights: We build an intersection energy consumption and emission model with signal priority strategy. The model can evaluate the environmental impact of signal priority strategy on intersection. Three SPSs, active, real-time and i-VICS based, are embedded in model for comparison. The i-VICS based SPS has the best environmental performance while providing priority. Abstract: A signal priority strategy (SPS) is implemented to encourage the development of public transportation, but this strategy may delay other vehicles to produce more emissions, especially at intersection. This study aims to develop an intersection energy consumption and emissions model framework with an embedded SPS to analyse the impacts of the SPS on the intersection. To validate this model framework, an intersection in Shenzhen, China was selected for simulation as a case study. In this study, we compared the effects of an active SPS, a real-time SPS and the real-time SPS improved under Intelligent Vehicle Infrastructure Cooperation System (i-VICS) on the energy consumption and emissions of the targeted intersection. The simulation results illustrate that, the active strategy could decrease fuel consumption and emissions with a maximum reduction of 13.33% in fuel consumption, and the real-time strategy maintains a smooth fluctuation in the total fuel consumption and emissions during the entire period. Compared with the two in-use strategies, the i-VICS-based transit priority strategy demonstrates the best environmental performance, by reducing the greatest negative environmental influences and cutting down the most emissions of nearly 28.86% in the case study. The developed intersection energy consumption and emissions model framework can be applied to evaluation of different SPSs on the environment respect, which can benefit to urban transportation management in a more sustainable way.